2017
DOI: 10.1111/nyas.13369
|View full text |Cite
|
Sign up to set email alerts
|

Attending, learning, and socioeconomic disadvantage: developmental cognitive and social neuroscience of resilience and vulnerability

Abstract: We review current findings associating socioeconomic status (SES), development of neurocognitive functions, and neurobiological pathways. A sizeable interdisciplinary literature was organized through a bifurcated developmental trajectory (BiDeT) framework, an account of the external and internal variables associated with low SES that may lead to difficulties with attention and learning, along with buffers that may protect against negative outcomes. A consistent neurocognitive finding is that low-SES children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 127 publications
(263 reference statements)
0
32
0
1
Order By: Relevance
“…To extend the existing knowledge on the combined effects of race and family SES on adolescents' outcomes, we built this study on the MDRs literature and compared racial groups of adolescents for the effects of family SES on school performance. We expected weaker effects of family SES on adolescents' attention, as a main predictor of school performance [30,74,75] for NHB than NHW adolescents.…”
Section: Aimsmentioning
confidence: 80%
See 1 more Smart Citation
“…To extend the existing knowledge on the combined effects of race and family SES on adolescents' outcomes, we built this study on the MDRs literature and compared racial groups of adolescents for the effects of family SES on school performance. We expected weaker effects of family SES on adolescents' attention, as a main predictor of school performance [30,74,75] for NHB than NHW adolescents.…”
Section: Aimsmentioning
confidence: 80%
“…High SES adolescents also have access to a wide range of educational and stimulating resources in their homes [ 26 ]. Finally, high SES adolescents are being raised in environments which are low in stress [ 27 , 28 , 29 , 30 , 31 ]. All these factors have strong positive effects on adolescents’ development [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that instead of intervening once problems arise, early interventions that have a remediating effect on the brain following early traumatic events can help to reduce the likelihood of negative outcomes (Bick & Nelson, 2016). This would include interventions that focus on self-regulation training (Schibli, Wong, Hedayati, & D'Angiulli, 2017) such as mindfulness (Marchand, 2014) and neurofeedback (van der Kolk, 2014; van der Kolk et al, 2016), in addition to the interventions that have already demonstrated success related to childhood adversity (e.g., trauma-focused cognitive behavioral therapy; Cohen et al, 2016). As an example, nascent research on mindfulness-based programs has begun to address potential neural mechanisms at play through this practice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the level of family income is the variable which most contributes to predicting the performance of the student on the ENEM, emphasizing that learning inequality in Brazil is related not only to the type of school the student attends but also to the family's socioeconomic level 21 . Moreover, the socioeconomic level has already been associated with cognitive development in childhood 22 . Thus, the data obtained suggest the need for specific performance standards for time and type of school.…”
Section: Discussionmentioning
confidence: 99%